(untitled) (Journal of Hama University, 2025)
This study aimed to test the presence of shocks or structural breaks in the real GDP growth rate series in Syria during the period (2000-2021). To achieve the study objective, a set of statistical tests were applied, firstly the Augmented Dicky-Fuller (ADF) test (1981) was applied to test the stability of the GDP growth rate series, then the Zivot-Andrews (1992) test was applied to test the stability in the presence of one structural break, and in order to ensure the presence of more than one structural break in the studied series, the Bai and Perron (1998-2003) test was applied. The study concluded that the GDP growth rate series is unstable according to the (ADF) test, and the Zivot-Andrews test indicated the presence of a negative structural break in the real GDP growth rate series in 2012, while the Bai and Perron test indicated the presence of a negative structural break in 2012 and a positive structural break in 2015.